DIGITAL TRANSFORMATION OF BUSINESS MANAGEMENT: INNOVATIVE MODELS, FORECAST SCENARIOS AND CURRENT CHALLENGES OF ECONOMY MODERNIZATION - I.V. Burtnyak; T.V. Khaludilo (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu)
The theoretical foundations of digital transformation in enterprise management have been substantiated in the article under conditions of dynamic market changes and globalization. It has been demonstrated that the traditional model of managerial processes and certain measures for the implementation of digital technologies are conflicted with contemporary challenges—global economic crises, tensions in international relations, and the rapid development of information technologies—which reduces enterprises’ ability to adapt to external shocks.